A Tinószemű, Kirké és az „istenek”: Borbély Szilárd Bukolikatájban című kötetének antik vonatkozásai - Krupp, József (Studia Litteraria, 2022)
Szilárd Borbély’s (1963–2014) collection of poems, Bukolikatájban (In a Bucolic Land), was published posthumously, eight years after the author’s death. In this collection, Borbély creates a bucolic world of his own, which is closely linked to the literary space known from his novel Nincstelenek (The Dispossessed). The aim of this study is to investigate the relationship of the collection to the oeuvre and to address the question of genre. The essay focuses on the role of the “gods”: the meaning of this word oscillates between man-gods and ‘actual’ gods, thereby creating a complex semantic game throughout the poems. By analysing the role of some specific mythological figures, the paper shows that the relationship of Borbély’s long poems to the tradition of idyll is ambivalent.